Sistem Pakar Diagnosa Penyakit Ayam Potong dan Petelur dengan Metode Dempster Shafer - Syahdad Eka Ramadhan; Jhonson Efendi Hutagalung; Suparmadi Suparmadi (Building of Informatics, Technology and Science (BITS), 2022)
At this time, chicken diseases often occur, especially for broiler and laying hens, so that it will cause a decrease in the production of meat and eggs. Diseases that attack chickens sometimes cannot be overcome by breeders because farmers do not understand the early symptoms of chicken illness, so farmers allow these conditions to cause chicken disease to get worse. If it gets worse then the disease will spread to other chickens quickly. Farmers also rarely consult with livestock extension workers at the Livestock Service Office of Asahan Regency and the agency cannot visit the farm because the road to the farm is far away and in a damaged condition. In order to be able to conduct good consultations between farmers and the service, it is necessary to design an application based on an expert system to facilitate farmers in diagnosing chicken diseases so that they do not have to come for consultation with livestock extension workers. With this web-based system used, it makes it easier for farmers to diagnose broiler and layer chicken diseases by simply selecting the symptoms that may be experienced by chickens in the system and the system will provide decisions about what diseases the chickens are experiencing. In the expert system application designed using data analysis with the Dempster Shafer method. The results of the decision with the case studied in the form of symptoms experienced by chickens resulted in 38.44% of snot disease, besides being able to determine the disease, this application can also provide a solution for handling it